Design and experimental research of pipeline stress measurement system based on alternating current field - Guangfeng QI; Xiyan LI; Xin TANG; Xin'an YUAN; Qing HAN; Anquan WANG; Wei LI; Keyu WANG (You-qi chuyun)
Ferromagnetic pipelines are prone to stress distortion during service, which will likely cause destructive defects, such as fatigue damage and cracks, and even major safety accidents in severe cases. This makes it particularly important to measure the stress distortion of ferromagnetic pipelines. Herein, a simulation model of pipeline stress measurement was established by the finite element software COMSOL based on the alternating current field stress measurement (ACSM) technology. Then, the characteristic signals were selected to represent the stress, which allowed us to explore the influence of probe excitation direction on stress measurement, find the optimal excitation mode, and analyze the signal variation law of the pipeline subjected to stress in different magnitudes and directions. Based on the simulation results and the characteristics of pipeline stress distribution, a set of ACSM based pipeline stress measurement system integrating the portable case and probe was designed and developed to test the tensile specimen of 45# steel and X70 steel pipeline within 0?105 MPa. The simulation and test results demonstrate that the selected characteristic signal could reflect the stress distortion because the stress distortion of pipeline causes the disturbance in electromagnetic field. The optimal excitation direction of the probe is perpendicular to the stress, and the designed portable ACSM based pipeline stress measurement system has been verified to be capable of detecting the stress distortion area of the pipeline. The research results are expected to provide references for the rapid measurement of stress distortion in ferromagnetic pipelines.